A microRNA‐7/growth arrest specific 6/TYRO3 axis regulates the growth and invasiveness of sorafenib‐resistant cells in human hepatocellular carcinoma. Issue 1 (29th November 2017) - Kabir, Tasnuva D.; Ganda, Clarissa; Brown, Rikki M.; Beveridge, Dianne J.; Richardson, Kirsty L.; Chaturvedi, Vishal; Candy, Patrick; Epis, Michael; Wintle, Larissa; Kalinowski, Felicity; Kopp, Christina; Stuart, Lisa M.; et al.
Abstract : Sorafenib remains the only approved drug for treating patients with advanced hepatocellular carcinoma (HCC). However, the therapeutic effect of sorafenib is transient, and patients invariably develop sorafenib resistance (SR). Recently, TYRO3, a member of the TYRO3‐AXL‐MER family of receptor tyrosine kinases, was identified as being aberrantly expressed in a significant proportion of HCC; however, its role in SR is unknown. In this study, we generated two functionally distinct sorafenib‐resistant human Huh‐7 HCC cell lines in order to identify new mechanisms to abrogate acquired SR as well as new potential therapeutic targets in HCC. Initially, we investigated the effects of a microRNA (miR), miR‐7‐5p (miR‐7), in both in vitro and in vivo preclinical models of human HCC and identified miR‐7 as a potent tumor suppressor of human HCC. We identified TYRO3 as a new functional target of miR‐7, which regulates proliferation, migration, and invasion of Huh‐7 cells through the phosphoinositide 3‐kinase/protein kinase B pathway and is markedly elevated with acquisition of SR. Furthermore, miR‐7 effectively silenced TYRO3 expression in both sorafenib‐sensitive and sorafenib‐resistant Huh‐7 cells, inhibiting TYRO3/growth arrest specific 6‐mediated cancer cell migration and invasion. Conclusion : We identified a mechanism for acquiring SR in HCC that is through the aberrant expression of the TYRO3/phosphoinositide 3‐kinase/protein kinase B signal transduction pathway, and that can be overcome by miR‐7 overexpression. Taken together, these data suggest a potential role for miR‐7 as an RNA‐based therapeutic to treat refractory and drug‐resistant HCC. (Hepatology 2018;67:216‐231)